Management of penile emergencies- one year observation - Sarker, Ashok Kumar; Babu, Tarafdar Habibullah; Ahmed, Abul Bashar Shahriar (International Surgery Journal, 2021)
Background: Penis is a very sensitive organ and even minor injury or discomfort may cause a patient to seek emergency evaluation. Penile emergencies and their management often rely on the results of imaging examinations. But most of the time the traumatic emergencies require urgent exploration to ensure a fair outcome. Objective was to present different types of penile emergencies and to determine the overall outcome of their managements. Methods: It was an observational study conducted at surgery department of Enam Medical College and Hospital, for one year. All patients with penile emergencies were included by selective sampling technique. The main outcome variables were type of penile emergencies, etiology of trauma, grading of trauma, types of surgical intervention, postoperative erectile function. Data processing and analysis were done using SPSS v (23). Statistical significance was determined by Students t test for quantitative data. Results: Total 33 patients admitted with emergencies. 18 (54.5%) belonged to traumatic category, 10 (30%) belonged to infective and one patient (3%) belonged to vascular (ischemic priapism) and others consist of 4 (12%). 40% of trauma was of grade III variety. Seven were victim of sharp cut injury. One who presented with ischemic priapism after 3 days underwent emergency distal shunt procedure with an acceptable functional penis post operatively. Timing of surgical intervention was compared with erectile function on the basis of International Index of Erectile Function (IIEF). A p value <0.05 was considered to be significant. Conclusions: Penile emergencies require prompt, accurate diagnosis. Early surgical intervention can save the organ.